2022
DOI: 10.1002/cam4.4978
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of clinical characteristics on risk and prognosis of synchronous brain metastases in small‐cell lung cancer patients: A population‐based study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Zhu et al [ 13 ] demonstrated that in NSCLC patients, young age (< 65), female, race, higher tumor grade, advanced T-stage or N-stage, liver metastasis, lung metastasis, bone metastasis were independent risk factors for developing SBM, while female, grade, early T stage, married status, no other site-specific metastases, other race, chemotherapy and radiation treatments were associated with significantly better mLCSS. In another retrospective study based on SEER database, Zhou et al declared that SCLC patients who are black, higher T stage, lung metastases and bone metastases had greater odds of SBM at initial diagnosis, and age ≥ 65, singled, higher T stage, higher N stage, liver metastases and bone metastases were independently related to shorter OS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [ 13 ] demonstrated that in NSCLC patients, young age (< 65), female, race, higher tumor grade, advanced T-stage or N-stage, liver metastasis, lung metastasis, bone metastasis were independent risk factors for developing SBM, while female, grade, early T stage, married status, no other site-specific metastases, other race, chemotherapy and radiation treatments were associated with significantly better mLCSS. In another retrospective study based on SEER database, Zhou et al declared that SCLC patients who are black, higher T stage, lung metastases and bone metastases had greater odds of SBM at initial diagnosis, and age ≥ 65, singled, higher T stage, higher N stage, liver metastases and bone metastases were independently related to shorter OS [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of brain metastases is 10-20% in patients with NSCLC at diagnosis, and the lifetime incidence has increased up to 50% as a result of an increase in patients' survival 11,12 higher N stage, liver metastases and bone metastases were independently related to shorter OS 14 .…”
Section: Impact Of Therapy On Os Of Patients With Sbmmentioning
confidence: 99%
“…Patients with BM were subsequently treated with palliative therapy. The standard treatment for SCLC BM is still WBRT, with an overall effective rate (ORR) of approximately 50% -80% ( 5 ). Magnetic resonance imaging (MRI) is a more sensitive technique to detect BM, In the MRI era, the estimated prevalence of BM increased by 14% ( 6 ).…”
Section: Introductionmentioning
confidence: 99%